Pendekatan Manajemen Biaya Untuk Meningkatkan Ketepatan Penghitungan Biaya Melalui Time Driven Activity Based Costing System - Listiadi, Agung (BISMA (Bisnis dan Manajemen), 2018)
Expense represent important factor in company and emulation in market. Consumer wil chosen producer capable to yield service and product owning high quality at the price of cheap. Management system of the Expanse of emphasizing at disclosure compared to alocation. And Management persuant to ctivity is heart of system operation of contemporaary operation. At least there is two primary factor which mus to be paid attention in location of tricker of expanse of (drifer cost) this is: expanse of correlation storey; level and measurement between driver cost with cunsumption of overhead real. Dreiver cost divided into two category, that is structural of cost driver and Cost driver executional represent base used to burden the expanse of which is gathered at pool cost to So that with calculation of expanse pass/through Time Driven costing activity-based, company obtain; get more accurate and precise information.